Mentha piperita protects against Cadmium induced oxidative renal damage by restoring antioxidant enzyme activities and suppressing inflammation in rats - prabu, Milton; pandiyan, Thanga; chanu, Sumedha N (International Journal of Pharmacology and Toxicology, 2013)
Background: The aim of this study was to investigate the possible protective role of the Mentha piperita leaf extract (MPE) on cadmium (Cd)-induced nephrotoxicity using biochemical and histopathological approaches. Methods: The control group received the vehicles only. The Cd treated group received Cdcl2 (5 mg/kg) orally in isotonic saline for 4weeks. Cd + MPE treated group received the MPE at a dose of (100mg/kg in 5% tween 80) along with Cd. MPE alone treated group received the MPE alone orally at a dose of 100mg/kg in 5% tween 80 for 4 weeks. Results: In experimental rats oral administration of CdCl2 (5 mg/kg) for 4weeks significantly induced renal damage which was evident from the increased levels of serum urea, uric acid and creatinine with a significant (p<0.05) decrease in creatinine clearance. Cd also significantly (p<0.05) decreased the levels of urea, uric acid and creatinine in urine. Cd-induced oxidative stress in kidney tissue was indicated by the increased levels of renal lipid peroxidation markers (thiobarbituric acid reactive substances and lipid hydro peroxides) and protein carbonyl content with a significant (p<0.05) decrease in non- enzymatic (total sulfhydryl group, reduced glutathione, vitamin C and E) and enzymatic antioxidants (superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GPx), glutathione S-transferase (GST), glutathione reductase (GR). Moreover the kidneys of Cd-treated rats also exhibit significantly (p<0.05) increased levels of tumor necrosis factor (TNF-?) and nitric oxide (NO). The histopathology of Cd treated rats showed tubular necrosis, degeneration, dilation, desquamation, thickening of basement membrane and luminal cast formation. MPE (100mg/kg/day) treatment markedly attenuated the Cd-induced biochemical alterations in serum, urine and renal tissue, and brings the TNF-? and NO in to normal levels. MPE also ameliorated the Cd-induced pathological changes when compared with Cd-alone-treated group. Conclusions: These results indicate that the natural dietary antioxidant MPE might have significant protective effect against Cd- induced oxidative stress mediated in rats. Due to its antioxidant and anti-inflammatory effects, it will provide an accessible and cheap traditional medicine source for treatment of Cd mediated environmental and occupational ailments.